Auto Oxidation Kinetics of Ascorbate by Cupric Ions - Troncoso, Luzmila (1998)
Ascorbate autoxidation catalyzed Cu2 + is performed via a first order reaction , a process that is dependent upon the concentration of Cu2 + and that follows a saturation emetic . This suggests that in the sequence an intermediate complex catalyst which would limit the formation of reaction products , one of which is a free hydroxyl radical is formed. Thiourea markedly inhibits autoxidation reaction , while it has no effect glycerol . Ascorbate and Cu2 + , used at concentrations that autoxidation occurs, do not cleave the disulfide bond of DTNB . Histidine and citrate inhibit both autoxidation reaction as breaking of the disulfide bond of DTNB . These results suggest that the rupture of the disulfide bridge of DTNB be realized with the intervention of the hydroxyl free radicals generated by the ascorbate system / Cu + , and in parallel by a process of reduction or hydrolysis .